Evolution of Graphene Patterning: From Dimension Regulation to Molecular Engineering - Wei, Tao; Hauke, Frank; Hirsch, Andreas (Advanced Materials, 2021)
The realization that nanostructured graphene featuring nanoscale width can confine electrons to open its bandgap has aroused scientists' attention to the regulation of graphene structures, where the concept of graphene patterns emerged. Exploring various effective methods for creating graphene patterns has led to the birth of a new field termed graphene patterning, which has evolved into the most vigorous and intriguing branch of graphene research during the past decade. The efforts in this field have resulted in the development of numerous strategies to structure graphene, affording a variety of graphene patterns with tailored shapes and sizes. The established patterning approaches combined with graphene chemistry yields a novel chemical patterning route via molecular engineering, which opens up a new era in graphene research. In this review, the currently developed graphene patterning strategies is systematically outlined, with emphasis on the chemical patterning. In addition to introducing the basic concepts and the important progress of traditional methods, which are generally categorized into top-down, bottom-up technologies, an exhaustive review of established protocols for emerging chemical patterning is presented. At the end, an outlook for future development and challenges is proposed.
CRIS-Team WoS Importer:2021-10-08